2022
DOI: 10.3390/jcm11164928
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD38 with Daratumumab Plus Chemotherapy for Patients with Advanced-Stage Plasmablastoid Large B-Cell Lymphoma

Abstract: Plasmablastic lymphoma (PBL) is a rare and aggressive form of large B-cell lymphoma (LBCL) most commonly seen in the setting of chronic immunosuppression or autoimmune disease. The prognosis is poor and CHOP-like regimens often fail to produce durable remission; therefore, there is no established standard of care treatment. However, PBL demonstrates substantial morphologic and immunophenotypic overlap with multiple myeloma (MM), suggesting that MM therapeutics might prove useful in treating PBL. We studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Finally, given the plasmablastic phenotype with CD138- and CD38-positivity, other therapies used in patients with multiple myeloma have been implemented. Lenalidomide in combination with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) [ 26 , 27 ] or daratumumab (monoclonal antibody against CD38) in combination with EPOCH demonstrated responses in selected patients with advanced PBL [ 28 ]. In relapsed or refractory cases of aggressive lymphoma, therapeutic options have also expanded to incorporate experimental immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given the plasmablastic phenotype with CD138- and CD38-positivity, other therapies used in patients with multiple myeloma have been implemented. Lenalidomide in combination with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) [ 26 , 27 ] or daratumumab (monoclonal antibody against CD38) in combination with EPOCH demonstrated responses in selected patients with advanced PBL [ 28 ]. In relapsed or refractory cases of aggressive lymphoma, therapeutic options have also expanded to incorporate experimental immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting CAMs such as CD38 and CD138/SDC1 with monoclonal antibodies have achieved promising results in multiple myeloma [ 30 , 31 ]. Daratumumab, a monoclonal antibody directed against CD38, was reported to be effective in advanced-stage large B-cell lymphoma (LBCL) with plasmablastic features [ 32 ]. In this study, four PBL patients achieved durable response (12–31 months and ongoing) after the treatment of daratumumab combined with DA-EPOCH [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daratumumab, a monoclonal antibody directed against CD38, was reported to be effective in advanced-stage large B-cell lymphoma (LBCL) with plasmablastic features [ 32 ]. In this study, four PBL patients achieved durable response (12–31 months and ongoing) after the treatment of daratumumab combined with DA-EPOCH [ 32 ]. Our results showed that the expression of CAMs was significantly higher in PBL than in DLBCL, suggesting that CAMs may play important roles in the development of PBL.…”
Section: Discussionmentioning
confidence: 99%
“…Ryu assessed the effectiveness and safety of daratumumab-based treatment plans in seven patients with advanced-stage PBL. 86 Out of these patients, 6 were considered evaluable, 4 had classic PBL, and 1 did not satisfy the precise criteria for PBL as established by the World Health Organization (WHO). 86 The initial assessment revealed that the median age of the patients included was 48 years.…”
Section: Daratumumabmentioning
confidence: 99%
“… 86 Out of these patients, 6 were considered evaluable, 4 had classic PBL, and 1 did not satisfy the precise criteria for PBL as established by the World Health Organization (WHO). 86 The initial assessment revealed that the median age of the patients included was 48 years. Additionally, all seven patients had disease locations outside the lymph nodes, 4 patients had ECOG scores of 3 or 4 at diagnosis, and 5 patients proved positive for CD38.…”
Section: Daratumumabmentioning
confidence: 99%